COVID-19 burden in Iran: disability-adjusted life years analysis from hospital data, 2020-2021 - Soheila Damiri; Mahshad Goharimehr; Mohammad Mahdi Nasehi; Mohammad Effatpanah; Zahra Shahali; Hossein Ranjbaran; Rajabali Daroudi (BMC, 2024)
Abstract Background The burden of disease based on disability-adjusted life years (DALYs) is one of the internationally accepted metrics for assessing the impact of a disease or injury on population health. This study aimed to provide evidence of the burden of COVID-19 on health in Iran based on hospital-level data from the Iran Health Insurance Organization (IHIO), which covers almost half of the country's population. Methods The data of all IHIO enrollees who were referred to hospitals across the country from the beginning of the COVID-19 pandemic (February 2020) to December 30, 2021, with assigned diagnosis codes of COVID-19, were extracted from the hospital information processing system. The DALYs due to COVID-19 were estimated using the standard approach of the World Health Organization and the European Burden of Disease Network guideline. Results In the years 2020 and 2021, among a population of about 42 million people, 1,040,367 individuals were admitted to the hospital due to COVID-19 infection, of whom 73% were hospitalized (760,963 patients). The total estimated DALYs for these two years were 665,823 and 928,393, respectively (1,603 and 2,234 per 100,000 population). 99.7% of DALYs were attributed to years of life lost due to premature death (YLLs). The share of the disease burden in the age groups of under 20 years, 20-49 years, 50-80 years, and over 80 years was 6.6%, 26.4%, 58.4%, and 8.6%, respectively. Conclusions Based on the hospital-level data estimates, COVID-19 has had a significant burden on health in Iran. COVID-19 was identified as the fifth leading cause of disease burden in Iran during the study period, ranking after cardiovascular diseases, psychological disorders, neoplasms, and musculoskeletal disorders. Additionally, COVID-19 was the third major cause of death, following cardiovascular diseases and neoplasms. Policymaking and the implementation of comprehensive programs to enhance the response of the health system and society to outbreaks of emerging and re-emerging infectious diseases are of utmost importance.